2019
DOI: 10.3390/jcm8112004
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Antibiotic Resistance in Iranian Helicobacter pylori Isolates: Importance of Functional and Mutational Analysis of Resistance Genes and Virulence Genotyping

Abstract: The high prevalence of antibiotic resistance in Helicobacter pylori has become a great challenge in Iran. The genetic mutations that contribute to the resistance have yet to be precisely identified. This study aimed to investigate the prevalence of antibiotic resistance and virulence markers in Iranian H. pylori isolates and to analyze if there is any association between resistance and genotype. Antibiotic susceptibility patterns of 68 H. pylori isolates were investigated against metronidazole, clarithromycin,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 86 publications
(155 reference statements)
4
20
2
Order By: Relevance
“…In the preset study, we also investigated the presence of various H. pylori virulence genotypes. In accordance with our previous studies in Iranian populations, we detected a high prevalence of vacA s1 (77.1%) and vacA m2 (65.7%) allelic genotypes [38,39]. The vacA s1 allele has been reported to be associated with more severe atrophic gastritis in peptic ulcer patients [40,41].…”
Section: Discussionsupporting
confidence: 91%
“…In the preset study, we also investigated the presence of various H. pylori virulence genotypes. In accordance with our previous studies in Iranian populations, we detected a high prevalence of vacA s1 (77.1%) and vacA m2 (65.7%) allelic genotypes [38,39]. The vacA s1 allele has been reported to be associated with more severe atrophic gastritis in peptic ulcer patients [40,41].…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Fatahi et al[ 32 ] (2019) tested a highly conserved region of dupA and showed a significant relationship between the occurrence of DU and the presence of an 112 bp segment of dupA in the Iranian population[ 32 ]. Another group from Iran studied the relationship between antibiotic resistance pattern and virulence genotype among 68 H. pylori strains and found that metronidazole resistance was significantly associated with the strains harboring cagA, sabA and dupA [ 33 ]. One study from Kurdistan region of Northern Iraq reported that cagA gene was significantly associated with peptic ulcer disease rather than dupA , which contradict the result of Hussein et al[ 29 ] (2008).…”
Section: Discrepancies Of Dupa With Clinical Outcomentioning
confidence: 99%
“…From the 131 articles, 65 were excluded for the following reasons: meta‐analysis, review, non‐original research, conference abstract and article without full text (n = 55), and non‐relevant data or no data for susceptibility testing or no resistance data (n = 10). Finally, 66 studies 4,16‐80 were included in this systematic review and meta‐analysis (Supplementary Table ).…”
Section: Resultsmentioning
confidence: 99%